Internalized stigma among cancer patients enrolled in a smoking cessation trial: The role of cancer type and associations with psychological distress. Issue 5 (19th November 2021) - Warner, Erica T.; Park, Elyse R.; Luberto, Christina M.; Rabin, Julia; Perez, Giselle K.; Ostroff, Jamie S.
Abstract: Purpose: Cancer patients who smoke may experience significant stigma due both to their disease, and negative attitudes and beliefs regarding smoking. We investigated whether internalized stigma differed between currently smoking cancer patients diagnosed with lung or head and neck cancers, other smoking related cancers, and non smoking‐related cancers, and whether internalized stigma was associated with psychological distress. Methods: This cross‐sectional analysis used baseline data on 293 participants enrolled in a multi‐site randomized smoking cessation intervention trial of patients with recently diagnosed cancer. Internalized stigma was assessed using five Internalized Shame items from the Social Impact of Disease Scale. Smoking‐related cancers included lung, head and neck, esophageal, bladder, kidney, liver, pancreatic, colorectal, anal, small intestinal, gastric, and cervical. We used multivariable linear regression to examine whether mean internalized stigma levels differed between individuals with lung and head and neck cancers, other smoking‐related cancers, and non smoking‐related cancers, adjusting for potential confounders. We further examined the association of internalized stigma with depression, anxiety, and perceived stress, overall and among cancer type groups. Results: Thirty‐nine percent of participants were diagnosed with lung or head and neck cancer, 21% with another smoking‐related cancer, and 40% with a non smoking‐related cancer. In multivariable‐adjusted models, participants with lung or head and neck cancers (11.6, 95% confidence intervals (CI) = 10.8–12.2; p  < 0.0001) or other smoking‐related cancers (10.7, 95% CI = 9.8–11.7; p  = 0.03) had higher mean internalized stigma scores compared to those non‐smoking‐related cancers (9.3, 95% CI = 8.6–10.0). We observed similar positive associations between internalized stigma and depressive symptoms, anxiety, and perceived stress among participants with smoking‐related and non smoking‐related cancers. Conclusions: Among smokers, those with smoking‐related cancers experienced the highest levels of internalized stigma, and greater internalized stigma was associated with greater psychological distress across cancer types. Providers should assess patients for internalized and other forms of stigma, refer patients for appropriate psychosocial support services, and address stigma in smoking cessation programs.